2005
DOI: 10.1007/s00213-005-2265-8
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of alprazolam on risky decision making in humans

Abstract: Alprazolam administration produced increases in human risk taking under laboratory conditions. In union with previous studies, the observed shift in trial-by-trial response probabilities suggests that sensitivity to consequences (e.g., oversensitivity to recent rewards) may be an important mechanism in the psychopharmacology of risky decision making. Additionally, risk-seeking personality traits may be predictive of acute drug effects on risk-taking behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 40 publications
3
31
1
1
Order By: Relevance
“…This includes demonstrations that manipulation of serotonergic (Rogers et al, 1999a(Rogers et al, , 2003, catecholamine (Rogers et al, 2004;Scarna et al, 2005) and GABAergic activity (Deakin et al, 2004;Lane et al, 2005a) can influence laboratory models of decision-making. However, at the current time, little is known about the importance of cannabinoid activity in decision-making despite the preponderance of CB 1 receptors within corticolimbic circuitry (Herkenham et al, 1990) and their interactions with other neuromodulatory systems (Ameri, 1999;Tanda et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…This includes demonstrations that manipulation of serotonergic (Rogers et al, 1999a(Rogers et al, , 2003, catecholamine (Rogers et al, 2004;Scarna et al, 2005) and GABAergic activity (Deakin et al, 2004;Lane et al, 2005a) can influence laboratory models of decision-making. However, at the current time, little is known about the importance of cannabinoid activity in decision-making despite the preponderance of CB 1 receptors within corticolimbic circuitry (Herkenham et al, 1990) and their interactions with other neuromodulatory systems (Ameri, 1999;Tanda et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Asimismo, algunos estudios en consumidores de esta sustancia han encontrado alteraciones en la impulsividad indicando comportamientos desinhibidos (Michel y Lang, 2003), toma de decisiones impulsivas (Dassanayake et al, 2012;Lane, Tcheremissine, Lieving, Nouvion, y Cherek, 2005), y déficits en la inhibición de respuesta (Acheson, Reynolds, Richards, y de Wit, 2006). Distintos modelos teóricos sobre adicción han señala-do la impulsividad como un marcador de vulnerabilidad de gran relevancia en la explicación de los procesos adictivos, tanto para explicar el inicio como el mantenimiento del consumo de drogas (Adan, 2002, Arce y Santisteban, 2006Cano-Cervantes, Araque-Serrano, y Cándido-Ortiz, 2011;Cortés-Tomás, Giménez-Costa, Motos-Sellés, y Cadaveira-Mahía, 2014;Gullo, Loxton, y Dawe, 2014;Navas, Torres, Cándido, y Perales, 2014;Pattij y De Vries, 2013).…”
Section: Impulsivity In Men With Prescription Of Benzodiazepines and unclassified
“…Deakin et al [2004] showed that a dose of the benzodiazepine val-520 ium increased the number of points wagered in a risktaking task in only those trials with the lowest odds of winning but the highest potential payoff. Lane et al [2005b] found that administration of the benzodiazepine alprazolam produced increased selection of a 525 risky option under laboratory conditions. The strength of subjects' risk-seeking personality traits may be predictive of how drugs affect their risk-taking behavior (Lane et al [2005b]).…”
Section: Hbhf_02_237633mentioning
confidence: 99%
“…Lane et al [2005b] found that administration of the benzodiazepine alprazolam produced increased selection of a 525 risky option under laboratory conditions. The strength of subjects' risk-seeking personality traits may be predictive of how drugs affect their risk-taking behavior (Lane et al [2005b]). …”
Section: Hbhf_02_237633mentioning
confidence: 99%